Monazite petrochronology constrains the metamorphic evolution of high-grade metamorphic rocks in the Dai Loc shear zone, Central Vietnam - Nguyen Duc, Nam; Ching-, Hua Lo; Tadashi, Usuki; Yoshiyuki, Iizuka; Mei-, Fei Chu; Jian-, Wei Lin; Pham, Binh (Vietnam Journal of Earth Sciences, 2026)
The Dai Loc shear zone in central Vietnam contains granulite-facies rocks and is a key area for studying the Early Paleozoic metamorphic evolution of the Indochina Block. An integrated study of in-situ geochronology, trace element geochemistry, and microtextural analysis was conducted to decipher the metamorphic evolution of this high-grade unit. Monazites from the two granulite samples display three distinct chemical domains, whose trace element compositions closely correlate with garnet growth and breakdown. Yttrium- and heavy rare-earth element (HREE)-rich monazite core domains are interpreted to have formed with limited garnet growth, recording a discrete growth episode during prograde metamorphism at ~435 Ma. Y- and HREE-poor domains are linked to significant garnet growth during peak conditions at ~420 Ma. The elevated Y+HREE concentrations in the outermost rim domains indicate their formation during garnet breakdown and likely date the retrograde metamorphism to ~390 Ma. These U–Pb monazite ages align well with the U-Pb zircon ages from granulites and syn-metamorphic granitoids in the study area, reinforcing the inferred metamorphic timeline. The results of this petrochronological study highlight the importance of integrating petrology with trace element data from major and accessory phases to link geochronological data to metamorphic P–T paths.